2021
DOI: 10.1111/jgh.15591
|View full text |Cite
|
Sign up to set email alerts
|

Lower incidence of COVID‐19 in patients with inflammatory bowel disease treated with non‐gut selective biologic therapy

Abstract: Background and Aim: Since the outbreak of COVID-19, concerns have been raised as to whether inflammatory bowel disease (IBD) patients under biologic therapy may be more susceptible to the disease. This study aimed to determine the incidence and outcomes of COVID-19 in a large cohort of IBD patients on biologic therapy. Methods: This observational retrospective multicenter study collected data about COVID-19 in IBD patients on biologic therapy in Italy, between February and May 2020. The main end-points were (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
19
0
1
Order By: Relevance
“…Moreover, in a retrospective multicenter study of IBD patients under biologics, non-gut-selective agents were associated with a lower incidence of COVID-19 infection and related symptoms compared with the patients on nonbiologic therapies (7.5% versus 18%, p < 0.001). Compared with the general population, IBD patients on biologic therapy are not exposed to a higher risk of COVID-19 [ 32 ]. A recent study showed that patients with COVID-19 infection who developed autoantibodies had higher severe COVID-19 outcomes [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a retrospective multicenter study of IBD patients under biologics, non-gut-selective agents were associated with a lower incidence of COVID-19 infection and related symptoms compared with the patients on nonbiologic therapies (7.5% versus 18%, p < 0.001). Compared with the general population, IBD patients on biologic therapy are not exposed to a higher risk of COVID-19 [ 32 ]. A recent study showed that patients with COVID-19 infection who developed autoantibodies had higher severe COVID-19 outcomes [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that the risk of developing severe COVID-19 may be lower in biological-treated patients potentially due to the effect of these drugs in suppressing cytokine inflammatory pathways that underlie COVID-19-associated inflammatory complications 30 56 59. In one meta-analysis, pooled relative risks of hospitalisation (RR 0.34, 95% CI 0.19 to 0.61), ICU admission (RR 0.49, 95% CI 0.33 to 0.72) and mortality (RR 0.22, 95% CI 0.13 to 0.38) were lower in biological-treated patients, most of whom were on anti-TNF, compared with patients treated with other non-biologicals for IBD 30.…”
Section: Impact Of Ibd On Covid-19mentioning
confidence: 99%
“…Indeed, evidence from a case series of patients with COVID-19 (but without IBD) has suggested that infliximab may help to combat severe COVID-19-induced cytokine storm syndrome by reducing systemic inflammation [ 83 ]. In addition, an observational study of Italian patients with IBD has reported that non-gut-selective agents (such as anti-TNF therapies) were associated with a lower incidence of SARS-CoV-2 infection, symptomatic COVID-19, and hospitalisations than were gut-selective biologics [ 88 ]. Consequently, there have been calls to investigate anti-TNF therapies as treatments for COVID-19 in clinical trials [ 89 ]: infliximab has recently been announced as one of three agents to be tested in hospitalised patients with COVID-19 in the World Health Organization’s Solidarity PLUS trial [ 90 ].…”
Section: Clinical Implications Of Sc Infliximab In the Covid-19 Pandemic Era And Beyondmentioning
confidence: 99%